Promotional elements and the performance of tourism marketing of visitor attraction places with the mediating role of public relations: empirical evidence from visitors in Ethiopia - Arega Enbiale Setegn; Gurudutta Pradeep Japee (Cogent Business & Management, 2025)
Tourism is a vital economic sector, yet many nations face challenges due to limited awareness and experience with efficient marketing techniques. This study examines the impact of promotional elements on tourism marketing effectiveness, with public relations serving as a mediator. Using cross-sectional empirical data from 370 visitors in Ethiopia, the model was estimated through structural equation modeling. The findings revealed that personal selling and advertising are significant drivers of tourism marketing success, with public relations playing a crucial mediating role that enhances their impact. Conversely, sales promotion had a minimal effect. These results underscore the need for strategic public relations initiatives to amplify the effectiveness of tourism marketing efforts. The study’s implications for tourism marketers and policymakers are: first, tourism marketers should integrate public relations with personal selling and advertising to optimize marketing strategies; second, policymakers must address the challenges in fully leveraging promotional tools. Future research could explore similar practices in different tourism contexts to deepen understanding of public relations’ role in tourism marketing. By implementing these recommendations, stakeholders can enhance their marketing strategies, improve communication, and achieve tremendous success in the competitive tourism landscape.